2018
DOI: 10.1016/j.cogdev.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evidence for 4-year-olds’ but not 2- and 3-year-olds’ false belief-related action anticipation

Abstract: HighlightsSignificant improvement in belief-related anticipation between the ages of 3 and 4.Children did not anticipate belief-related actions correctly until the age of 4 years.Correct anticipation only when the agent believed the object to be in its last location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 24 publications
(86 reference statements)
10
51
1
Order By: Relevance
“…It is not only the underlying processes, but also the exact developmental trajectory and potential limitations of implicit ToM processes that remain an open question. Recent studies have had difficulty replicating findings from different implicit ToM tasks (51)(52)(53), have reported considerably later developmental onsets of success in these tasks (53), and have reported specific performance limitations (53,54). Behavioral success in the current MRI sample was also weaker than in the original behavioral study of our implicit ToM paradigm (27), which likely resulted from reduced power in the smaller sample of children with usable MRI data.…”
Section: Discussionmentioning
confidence: 73%
“…It is not only the underlying processes, but also the exact developmental trajectory and potential limitations of implicit ToM processes that remain an open question. Recent studies have had difficulty replicating findings from different implicit ToM tasks (51)(52)(53), have reported considerably later developmental onsets of success in these tasks (53), and have reported specific performance limitations (53,54). Behavioral success in the current MRI sample was also weaker than in the original behavioral study of our implicit ToM paradigm (27), which likely resulted from reduced power in the smaller sample of children with usable MRI data.…”
Section: Discussionmentioning
confidence: 73%
“…Although it remains unclear which factors impact replicability with human participants, researchers have proposed that several procedural differences between studies may be responsible (24). Of special note, one interesting result from previous replication studies is that, while some researchers found a chance-level effect for FB2 (26), others found a below-chance effect for FB2 (as well as an above-chance effect for FB1) in the DLS results (23,25). One interpretation for this puzzling pattern is that human participants showed a location bias: they may have simply looked at the last location that the object inhabited (before it was finally removed).…”
Section: Discussionmentioning
confidence: 99%
“…In FB2, the actor watched the object be hidden in one location and then was absent when the object was moved to the second and ultimately removed. Although Senju et al used the FB1 design of Southgate et al, we decided to instead use the FB2 design because recent attempts to replicate Southgate et al with human populations found greater difficulty replicating the FB2 design (23)(24)(25)(26). We, thus, thought that the FB2 design would constitute a more stringent test of action anticipation in great apes.…”
Section: Significancementioning
confidence: 99%
“…… [T]hese findings suggest that executive function figures in coordinating perspectives more generally, not only epistemic ones, and in particular in coordinating others’ and one’s own conflicting perspectives” ( 71 , abstract). It is perhaps relevant that one recent study found that executive function does not correlate with performance in infant false-belief tasks (perhaps because they do not involve any coordinations), but it does correlate with classic false-belief tasks ( 72 ).…”
Section: Evidence For the Theorymentioning
confidence: 99%
“…Several studies have followed young children longitudinally from infancy to early childhood and correlated various measures of their early social cognition and interaction with their later false-belief understanding. Given that understanding false beliefs requires as a prerequisite the imagining and tracking of basic mental states, it is not surprising that some studies have found correlations between infants’ ability to track the perceptions and intentions of others, including in infant false-belief tasks, and their ability later, as young children, to understand false beliefs ( 75 ), although, as noted above, others have found no such correlation ( 72 ). However, most important to the current hypothesis, several longitudinal studies have found strong correlations between infants’ skills in joint attention and their later skills in classic false-belief tasks (e.g., 75 77 ).…”
Section: Evidence For the Theorymentioning
confidence: 99%